Collective Memory and Colloquial Aesthetic Experience. Remarks on the Functions of Digitalized Paintings in Second Life - Kaźmierczak, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Collective Memory and Colloquial Aesthetic Experience. Remarks on the Functions of Digitalized Paintings in Second Life The article addresses the representation of art in Second Life. There is an interesting dichotomy between collective memory and colloquial aesthetic experience in virtual reality. The article consists of two main parts: the first pertains to decontextualisation as a paradigm in art; the second refers to the features of daily aesthetic experience. The main hypothesis of this paper is: digitalized images of paintings reveal changes in thinking about art in a world dominated by new media (and thus also by Second Life). This hypothesis confi rms the presumption that collective memory nowadays is dominated by colloquial thinking about art, aesthetic and beauty.